How the United States government sacrifices athletes` constitutional rights in the pursuit of national prestige - Koller, D. L. (Brigham young university law review, 2008)
This Article is about the United States Government trading off athletes` constitutional rights in the pursuit of national prestige through sport. The Olympic Movement has for decades provided an incentive for governments of all ideologies to use elite athletes to enhance national prestige or demonstrate national supremacy. This phenomenon is commonly known as "sportive nationalism." Unlike countries such as the former East Germany and Soviet Union, the United States Government has not readily acknowledged its own practice of sportive nationalism, preferring instead to assert that Olympic Movement sport in the United States is a private endeavor. This Article, however, demonstrates that the United States has in fact practiced its own brand of sportive nationalism—previously as a foreign policy tool during the Cold War and today as part of the worldwide fight against athletic doping. This Article explains that the practice of United States sportive nationalism is accomplished through the United States Olympic Committee and now the United States Anti-Doping Agency, both of which serve as "private" Olympic Movement regulators. This private sector status of sport regulation in the United States has created a significant accountability vacuum so that manifestations of sportive nationalism that threaten athletes` eligibility, like the war on doping, largely go unchecked. As a result, athletes` constitutional liberty and property interests are threatened because there is no incentive to give, and in fact athletes are not given meaningful due process protections to protect their eligibility. Accordingly, this Article argues that steps should be taken to promote greater accountability for sportive nationalism in the United States Olympic Movement, so that the athletes who serve to enhance our nation`s prestige do not risk their due process rights in the process.